2017
DOI: 10.1108/ijhcqa-01-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Service quality, patient satisfaction and loyalty in the Bangladesh healthcare sector

Abstract: Purpose The purpose of this paper is to investigate service quality, patient satisfaction and loyalty in Bangladesh's healthcare sector. It identifies healthcare quality conformance, patient satisfaction and loyalty based on demographics such as gender, age and marital status. It examines the differences between public and private healthcare sectors regarding service quality, patient satisfaction and loyalty. Design/methodology/approach The authors distributed 450 self-administered questionnaires to hospital p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 31 publications
8
58
0
Order By: Relevance
“…Some literature has discussed the impact of service quality on loyalty, for instance, Ismail, et al [4] . Some have discussed the relationship between service quality, service satisfaction, and service loyalty such as Kondasani and Panda [5] , Fatima et al [6] , Ahmed et al [7] , as well as Meesala and Paul [8] . And some have analyzed the relationship between patient value, service satisfaction, and service loyalty, for example, Rahmani et al [2] and Miao et al [3] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature has discussed the impact of service quality on loyalty, for instance, Ismail, et al [4] . Some have discussed the relationship between service quality, service satisfaction, and service loyalty such as Kondasani and Panda [5] , Fatima et al [6] , Ahmed et al [7] , as well as Meesala and Paul [8] . And some have analyzed the relationship between patient value, service satisfaction, and service loyalty, for example, Rahmani et al [2] and Miao et al [3] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…To summarize, the extant Chinese studies focus more on public health service institutions rather than private institutions. Even if some studies focus on the private health service institutions, for example, Kondasani and Panda [5] , Ahmed et al, [7] , and Fatima et al [6] , these studies are not conducted in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study identified that the satisfaction of patients act as a mediator factor between repatronage intention and quality of service (Yeo et al, 2013). (Ahmed et al, 2017 andFatima et al, 2018) have found that the satisfaction of patients is significantly contributed to improve the relationship among loyalty and quality of service in the healthcare sector.…”
Section: Patient Satisfaction As Mediator Variablementioning
confidence: 99%
“…Expectation is a potential predictor for satisfaction, meaning that if the elderly are satisfied with the health services provided in the posbindu, they will visit the posbindu regularly. 8,9 The definition of the elderly's expectations towards the services in the posbindu has not yet been constructed but the definition of expectation itself can be adapted from the definition of expectation towards health services from Levenstein: "the individuals' stated reasons for the visit, that often relate to a symptom or a concern, which is anticipated for an acknowledgement or a response from the physician". 10 The classification of expectation is in an undergoing debate.…”
Section: Introductionmentioning
confidence: 99%